Effects of Cyclic Boil-Dry Treatment on Properties of Bintangor (Callophyllum Sp) Laminated Veneer Lumber - Chuo, Toung Wrn (2004)
This study evaluates the physical and mechanical properties of bintangor (Callophyllum sp) laminated veneer lumber (LVL) under cyclic boil-dry (CBD) treatment. The properties studied were thickness swelling (TS), linear expansion (LE), water absorption (WA), delamination, bending shear and static bending (moduli of elasticity and rupture). LVLs of 1220 x 2440 mm in size were manufactured on a commercial LVL production line. The thicknesses of the veneers were set at 3.1 and 4.1 mm, producing 17- and 13-ply LVL panels respectively. A total of two hundred and sixty four large specimens were prepared for static bending (50 x 90 x 1000 mm) and bending shear (40 x 50 x 300 mm). To determine the effect of sample size, seventy two small static bending specimens (12.5 x 50 x 305 mm) were cut from the 13-ply LVL. The small and large static bending specimens were tested according to American Society for Testing and Materials D 143 and AS/NZ 4063:1992 Timber – Stress-graded – in-grade strength and stiffness evaluation respectively. Bending shear was determined according to AS/NZ 4357. In all cases, the CBD treatment procedure was conducted by taking consideration the size factor so that each specimen would experience similar degree of heating regime. The analysis of variance (ANOVA) shows that the TS, delamination, stiffness (MOE) and strength (MOR) were significantly influenced by the specimen size, veneer thickness and number of CBD cycle while bending shear were significantly influenced by the number of CBD cycle and veneer thickness. The most severely degraded were specimens that have been treated for 10 cycles. LVL produced from thinner veneers (3.1 mm) as in 17-ply LVL, was apparently more stable where acceptably low TS, WA, LE and percent delamination were recorded resulting in low reductions in stiffness, strength and shear after CBD treatment. There was a negative relationship between delamination and bending shear after CBD treatment where 17-ply LVL showed a curvilinear trend whilst 13-ply LVL showed a linear relationship. The study also found inspite having the same degree of heating regime, larger specimens experienced much more severe strength degradation which mainly caused by shear failure at the center (middle layers) of the LVL panel. The shorter span used for the large specimens (1: 10) was observed to be responsible for the shearing effect that subsequently reduced the MOE and MOR values in this study. The outdoor aging revealed that MOE of smaller specimens was badly degraded (40%) compared to the large specimens (22%) after six months of outdoor aging. Large and small specimens produced from 13-ply LVL (thicker veneers) experienced more strength reduction under 6 months outdoor aging (28%) compared to 10 cycles of CBD treatment (24%). MOE and MOR after any one of 2, 5 or 10 cycles of CBD treatment showed good correlation with MOE and MOR after 3 and 6 months of outdoor aging.